VOSVIEWER SOFTWARE AS A TOOL IN ANALYZING THE BIBLIOMETRIC OF WATCHKEEPING ONBOARD SHIPS - Sulistiyowati, Ely; Kundori, Kundori; Indriyani, Kristin Anita; Nurhidayati, Indah (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
This article aims to conduct bibliometric research on ship crew members who carry out guard duty on ships. Research gaps in watch keeping studies are identified and analyzed. Ship crews carrying out guard duty must ensure ship safety and avoid the risk of ship accidents. The method used in this research is descriptive qualitative, namely by describing data visualization. The keyword chosen is "watch keeping". Data was collected from journals that have been published in Scopus indexed journals using publish or perish (PoP) and completed using Mendeley. Next, the data is input into VOS viewer. The results obtained from the publish or Perish search found as many as 200 articles on the topic of watch keeping published in the period from 1960 to 2023. Next, the results of data processing with VOS viewer obtained results based on keywords divided into 6 clusters. Overall, bibliometric analysis on the topic of watch keeping provides important insights into the research analyzed, which will help researchers, practitioners and policy makers understand the latest developments which are increasingly dynamic and continue to develop. The implementation of good and correct guard duty on a ship is by carrying out monitoring planning, responding to emergencies, carrying out effective communication, being alert to potential dangers while the ship is sailing, arranging rest times, and maintaining equipment on the ship so that it functions properly.